2017
DOI: 10.1186/s12916-017-0859-8
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomized trial to reduce caesarean delivery rates in Quebec: cost-effectiveness analysis

Abstract: BackgroundWidespread increases in caesarean section (CS) rates have sparked concerns about risks to mothers and infants and rising healthcare costs. A multicentre, two-arm, cluster-randomized trial in Quebec, Canada assessed whether an audit and feedback intervention targeting health professionals would reduce CS rates for pregnant women compared to usual care, and concluded that it reduced CS rates without adverse effects on maternal or neonatal health. The effect was statistically significant but clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
0
16
0
4
Order By: Relevance
“…Subjects with diabetes are known for carrying a disproportionately higher risk of CV disease when compared to non-diabetic subjects. In fact, a significant proportion of T2D patients experience clinical remission of the disease after several bariatric surgical interventions, such as RYGB, along with a significant improvement of several independent CV risk factors, including blood glucose levels, blood pressure and lipid profile, which synergistically result in an overall decrease of the estimated CV risk ( 14 ). Moreover, the weight loss profile of patients with T2D diagnosed prior to RYGB surgery was no different from non-diabetic patients, reinforcing the effectiveness of this weight reducing intervention in T2D patients and the likely dissociation of the observed effects in what concerns body weight and CV risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with diabetes are known for carrying a disproportionately higher risk of CV disease when compared to non-diabetic subjects. In fact, a significant proportion of T2D patients experience clinical remission of the disease after several bariatric surgical interventions, such as RYGB, along with a significant improvement of several independent CV risk factors, including blood glucose levels, blood pressure and lipid profile, which synergistically result in an overall decrease of the estimated CV risk ( 14 ). Moreover, the weight loss profile of patients with T2D diagnosed prior to RYGB surgery was no different from non-diabetic patients, reinforcing the effectiveness of this weight reducing intervention in T2D patients and the likely dissociation of the observed effects in what concerns body weight and CV risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Caesarean delivery rate above the WHO’s upper recommended rate of 15% [ 4 ] has not resulted with an improvement in neonatal outcomes but with an increase in maternal morbidity [ 5 7 ]. Indeed, caesarean sections lead to an appreciable increase in maternal complications in the short term (thromboembolism, infection, trauma, bleeding) and long term (risk of ectopic pregnancy, infertility, abnormal placental insertion, risk of uterine rupture) [ 8 , 9 ] and an increase in health costs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One recent observational study[ 30 ] was conducted to compare a risk of hospitalization for CVDs between gliptins with glimepiride using database of Korean National Health Insurance Service of 19,951 in cohort. This study reported that risk of hospitalization for CVDs was found to be decreased among patients with a history of visit for CVDs in the DPP-4 inhibitors versus glimepiride group.…”
Section: Urrent E Vidence Rmentioning
confidence: 99%